INVESTIGATING THE ROLE OF NURSING INTERVENTIONS IN REDUCING HOSPITAL ACQUIRED INFECTIONS. - Muteb Marzouq Mater Alayt , Nouf Mohammed Alshallali , Rami Ibrahim Alalawiy , Mubarak Mesfer Alorem , Abdullah Shallan Al Roman , Zahra Omar Ali , Mashael Ali Jeadi , Seetah Modhe Saleman , Hatim Ibrahim Al Hatim ,; Faisal Dakeel Mohammed Aljohani , Nasser Sanad Alsanani , Aljoharah Zaid Binnamshan,Mishary Masood R Alotibi,Ghadeer Mohammad Eid Almohammady,Abdallah Hawag Noman Algmele, (Chelonian Research Foundation, 2022)
This review emphasizes how important nurses are to the prevention of infections in hospital settings. As front-line healthcare providers, nurses use evidence-based practices to safeguard patient safety and prevent infections. Nursing practices have a major role in lowering healthcare-associated infections (HAIs) by promoting strict hand hygiene, the use of personal protective equipment (PPE), and adherence to cleaning standards. They are responsible for informing patients, relatives, and coworkers about infection control practices, lobbying for infection prevention, and influencing organizational policies. A key factor in creating safer healthcare environments and improving patient outcomes is the ethical duty nurses have to promote health and avoid sickness. This synopsis highlights the diverse roles that nurses play in infection control and underscores how important it is for them to lessen the effects of HAIs on patients and healthcare systems. Key words: Nurses, Infection control, Hospital, Healthcare associated infections, Cleaning.